Development of Mind Mapping Media to Improve Short Story Writing Skills in Elementary Students - Sabila, Ilma Husnul; Rambe, Riris Nurkholidah (Journal of Social Work and Science Education, 2025)
This research aims to develop teaching materials based on concept maps to improve the short story writing skills of fifth-grade students at MIS Ar-Rahman Tanjung Morawa, who previously faced difficulties in the use of spelling, critical thinking skills, text structure understanding, and writing interest. This type of research is Research and Development (R&D) using the ADDIE model. Data were collected through observations, interviews, questionnaires, and tests (pretest and posttest). Validation was conducted by experts in material, media, and language, followed by a practicality test involving students and teachers. The results of the validation showed a very high feasibility level, namely 90.91% (material expert), 84% (media expert), and 82.5% (language expert). The practicality test scored 86% from students and 91% from teachers. The teaching materials proved effective in improving short story writing skills and students’ learning motivation. The development of teaching materials using a combination of mind mapping and interactive visual design facilitates students in understanding story structure, organizing ideas, and writing texts creatively. Teachers can use these teaching materials as engaging learning media that are easy to adapt to various content contexts, while schools can utilize them to encourage more interactive and student-centered writing learning. This research enriches the literature on the application of mind mapping in narrative writing education at the elementary school level and provides empirical evidence that a conceptual visual approach can enhance students’ literacy skills.